About half of Ethiopian midwifery professionals reported being dissatisfied with their jobs: A systematic review and meta-analysis - Dagne Deresa Dinagde; Shambel Negesa marami; Gizu Tola Feyisa; Bekem Dibaba Degefa (Elsevier, 2024)
Background: Increasing well qualified health professionals is a part of sustainable development goal to specially to decrease maternal mortality below 70 per 100,000 deaths. Contrarily, The Nursing and midwifery councils (NMC) expect that 36% of healthcare workers, especially midwives, are leaving their jobs due to high turnover rates and job unhappiness worldwide. Methods: Studies were rigorously searched utilizing international databases from PubMed, Google Scholar, Cochrane Library, and Embase. Using the New Castle Ottawa scale for a cross-sectional study design, the quality of the articles that were searched was evaluated. The systemic review was conducted using the random effect approach, and statistical analysis was done using STATA version 17 software for the window. The Preferred Reporting Item for Systematic Review and Meta-Analyses (PRISMA) guideline was followed for reporting results. Results: A total of nine observational cross-sectional studies were included in this review. The pooled level of job satisfaction among midwives in Ethiopia was 52.2% (95% CI =41.7, 62.9). The pooled odds ratio showed that a significant positive association was found between midwives' job satisfaction and studied variables. Male midwife (OR = 0.45; 95% CI: 0.04, 0.87), fair supervision (OR = 2.03; 95%CI: 1.58-1), workload (OR = 1.72; 95%CI: 1.102-2.43) and motivation (OR = 1.64; 95%CI: 1.02-2.25) were strongly associated with job satisfaction. Conclusion: Evidence suggested that motivating employees, providing fair supervision, fair workloads, and fostering positive relationships with managers are all crucial tactics for retaining and enhancing the satisfaction of health professionals at health care facilities in Ethiopian.